Judaism for Gentiles Reading Paul beyond the Parting of the Ways Paradigm - Runesson, Anders (Mohr Siebeck, 2023)
For almost two millennia, readers of the New Testament have been trying to figure out Paul. The struggle with his words begins already within the canon itself. While Acts portrays with ease a Torah-observant, Pharisaic-messianic Paul working in partnership with James and other leaders in Jerusalem, the author of 2 Peter famously admitted that the apostle to the nations is difficult to understand. From that moment on debate has ebbed and flowed on all things Pauline; on women as leaders in assemblies and on the status of Jews and Gentiles in God's plan, just to mention two of the contentious topics associated with Paul. For clergy, scholar, and lay person, Paul's letters hold weight and continue to draw in new readers. Anders Runesson seeks to listen to the voice of the historical Paul - a Jew proclaiming a form of Judaism to non-Jews to save them from divine wrath - but also to probe what it means to breathe new life into this historical figure in the twenty-first century. "The Paul-within-Judaism movement is here to stay, and Anders Runesson is arguably its most hermeneutically sophisticated spokesperson. In this remarkable book, Runesson expertly guides us through difficult questions of social history, exegesis, ancient reception history, and modern constructive theology, all of which we need in order to understand Paul 'beyond the parting of the ways paradigm.'" Matthew V. Novenson, University of Edinburgh "In this compelling book, Anders Runesson incarnates Roman-period types of Judaism-thus, the seedbed of later Christianities-within their institutional matrix, the ancient synagogue. Radically reconceiving the so-called "parting of the ways," he traces a developmental arc from Paul through Theodosius I to explore how and why this apocalyptic Jewish movement, with its odd outreach to ethnic others, became the anti-Jewish arm of the late Roman state. If new ideas are food for thought, Runesson has served a feast." Paula Fredriksen, author of "Paul, the Pagans' Apostle" "This is the mature fruit of intensive research over a significant period of time, drawing together Runesson's explorations on Paul and Pauline theology, locating him firmly within his Jewish context on the one hand, and taking seriously that he is addressing gentiles. The historical depth and methodological rigor as well as the key awareness of hermeneutical presuppositions render this a rich and challenging source for scholars and students alike. But this is not only another academic contribution to the important field of Pauline studies, Runesson demonstrates how this approach to Paul is also relevant for theologizing in contemporary churches and interreligious interaction today. Thus the volume is a must for all engaged in Pauline Studies as well as in contemporary church and interreligious work." Kathy Ehrensperger, Abraham Geiger Kolleg, Potsdam "In recent years, Anders Runesson has emerged as a leading voice in the (distinct but related) projects of reading Matthew and Paul "within Judaism." In this significant volume on Paul, he draws on material from a number of his previous articles and book chapters, working it into a cohesive and comprehensive account of Paul's "Judaism for gentiles" and its place within a larger interpretive horizon. Over against approaches that see Paul as the architect of a "parting of the ways," Runesson understands him as working towards a "joining of the ways"-mixed groups of Jewish and gentile Christ-believers existing within the larger environment of Jewish diaspora synagogues. An impressive achievement, highly recommended." Terence L. Donaldson, Professor Emeritus, Wycliffe College, University of Toronto "In these important essays, Anders Runesson provides readers with an account of a thoroughly embodied and socially embedded Paul, a first-century Jewish Messiah follower seeking to live in the Roman world. The volume is a must read for anyone interested in thinking about the historical Paul." Matthew Thiessen, McMaster University, Hamilton "Anders Runesson takes his readers beyond the familiar constructions of Paul, significantly advancing the discussion of how to understand him and his movement. Historical and textual details are interrogated with clear, methodological discipline. The investigation is thoughtful, engaging, and accessible to informed non-specialists as well as scholars." Mark D. Nanos, PhD, University of St. Andrews, Scotland, author of "Reading Paul within Judaism" "Anders Runesson's essays impress for three reasons: First, by breaking with classical models of explanation, his handling of the reconstruction of early Christianity is not only innovative, but when set against the backdrop of historical and hermeneutical considerations, opens up further approaches and new perspectives. Second, because he is well-versed in dealing with literary and archaeological sources, Runesson is skillfully able to reorganize and interpret these factors. And finally, his contributions provide such a welcome interest in historical and theological research that even those who do not agree with all the results are constantly challenged to revisit well-trodden paths in search of fresh insights." Markus Öhler, University of Vienna "Anders Runesson here presents a must-read for Pauline scholars. It is remarkable how much ground this book covers and masters in a thought-provoking way. It is almost like an advanced handbook on several issues pertaining to Paul. This is an in-depth study on matters of method, history of interpretation, historical context, Pauline mission, women in the letters, the Pauline legacy and hermeneutics, to mention some key issues being addressed. The book achieves the purpose of a scholarly book as it triggers questions and further discussions. These questions and discussions may not always embrace Runesson's conclusions, but they will certainly be refined if this book is a constant dialogue partner, setting an agenda for how Paul's theology and mission can be adressed." Karl Olav Sandnes, MF Norwegian School of Theology, Religion and Society